2008
DOI: 10.1002/sia.2923
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of polyester by oxygen‐ and nitrogen‐plasma treatment

Abstract: In this paper, we present a study on the surface modification of polyethyleneterephthalate (PET) polymer by plasma treatment. The samples were treated by nitrogen and oxygen plasma for different time periods between 3 and 90 s. The plasma was created by a radio frequency (RF) generator. The gas pressure was fixed at 75 Pa and the discharge power was set to 200 W. The samples were treated in the glow region, where the electrons temperature was about 4 eV, the positive ions density was about 2 × 10 15 m −3 , and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
207
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 259 publications
(239 citation statements)
references
References 48 publications
18
207
2
Order By: Relevance
“…Many authors agree that probability for surface de-excitation of molecules with the excitation energy of only 1 eV is always low and practically independent from characteristics of solid materials. On the other hand, the literature on interaction between neutral oxygen atoms and solid materials abounds [76][77][78][79][80].…”
Section: Plasma Treatment Of Cellulose Wound Dressingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors agree that probability for surface de-excitation of molecules with the excitation energy of only 1 eV is always low and practically independent from characteristics of solid materials. On the other hand, the literature on interaction between neutral oxygen atoms and solid materials abounds [76][77][78][79][80].…”
Section: Plasma Treatment Of Cellulose Wound Dressingmentioning
confidence: 99%
“…This observation is sound with effects reported in appropriate literature. Namely, many authors have shown that a treatment of organic materials with gaseous plasma leads to increased surface roughness [77,[81][82][83]. While the effect is not yet fully understood, a plausible explanation is selective interaction with amorphous and crystalline segments of cellulose materials.…”
Section: Plasma Treatment Of Cellulose Wound Dressingmentioning
confidence: 99%
“…This new morphology is advantageous for following coupling processes due to an increased surface area and roughness [5]. In fact, the generated pattern on the sample 2 surface is a consequence of competition between functionalization and ablation phenomena both leading to surface restructuring [8]. The occurrence of ablation is ascertained via gravimetric means where a weight loss of ^4fjugcm -2 has been observed due to the plasma treatment for 15 s implying an etching rate of ~2 nm/s taking into account the density of the PVC grade used.…”
Section: Surface Morphology Analysismentioning
confidence: 99%
“…This multistep approach has aroused great interest thanks to several advantages such as convenient and controllable introduction of biocidal species with a high surface density together with precise localization and long stability of the grafted layers [6,7]. In the first phase, a preliminary functionalization has to be achieved regarding an inherent lack of active entities on the pristine substrate, where low temperature-atmospheric pressure plasma treatment has been proved to be effective therein [8,9]. However, the necessity to shorten the treatment duration to a few seconds calling for rather high plasma power density remains a critical impediment to largescale applications of this type of plasma [10].…”
Section: Introductionmentioning
confidence: 99%
“…The plasma treatment modifications of the PET surfaces are frequent in order to improving wettability [10] or water-repellent improvement [11]. Consequently, the treatment goals are very often functional water compatible group binding, such as -COOH, -OH, -NH2 [7][8][9][12][13][14][15][16][17][18][19][20][21], or Ti02/ Mo03 [22]. Moreover, the amine (-NH2) groups are very important for chemical reactions with proteins or surface interactions with cells [1].…”
Section: Introductionmentioning
confidence: 99%